Walter Kauders papers - Kauders, Walter, 1889-1985.
Military and medical records and notes relating to medical treatment received by Kauders for head injuries sustained during World War I and the official investigation conducted into the treatment at neurologist Julius von Wagner-Jauregg's clinic in Vienna, Austria. Also includes a letter and essay by Kauders predating the war.
Editor, army officer, and artist.
In German and Polish.
Forms part of: Sigmund Freud collection.
Keywords: Wagner-Jauregg, Julius von, -- 1857-; Neurology -- Austria -- Vienna; World War, 1914-1918 -- Medical care; Army officers; Artists; Editors